2000
DOI: 10.1007/s002530000424
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of an activated-sludge microbial consortium by selective biostimulation

Abstract: Our previous study showed that an activated-sludge process broke down at the phenol-loading rate of 1.5 g l(-1) day(-1), when non-flocculating bacteria (called R6T and R10) overgrew the sludge, resulting in a sludge washout. In this study, we attempted to circumvent this breakdown problem by reclaiming the consortium structure. Activated sludge was fed phenol, and the phenol-loading rate was increased stepwise from 0.5 g l(-1) day(-1) to 1.0 g l(-1) day(-1) and then to 1.5 g l(-1) day(-1). Either galactose or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On day 35, 20 days after inoculation, the activated sludge was subjected to a shock loading with phenol at 2.0 g l −1 day −1 . Our previous study (Watanabe et al ., 2000) has shown that phenol was discharged from the activ‐ated sludge unit immediately after the loading rate was increased to 2.0 g l −1 day −1 , even after the sludge had been sufficiently acclimatized to phenol. Figure 2B shows that phenol was promptly discharged from the non‐inoculated control, rN7‐inoculated and R5‐inoculated units after the shock loading at 2.0 g l −1 day −1 , whereas the rN7(R503)‐inoculated unit could cope with this shock loading.…”
Section: Resultsmentioning
confidence: 93%
“…On day 35, 20 days after inoculation, the activated sludge was subjected to a shock loading with phenol at 2.0 g l −1 day −1 . Our previous study (Watanabe et al ., 2000) has shown that phenol was discharged from the activ‐ated sludge unit immediately after the loading rate was increased to 2.0 g l −1 day −1 , even after the sludge had been sufficiently acclimatized to phenol. Figure 2B shows that phenol was promptly discharged from the non‐inoculated control, rN7‐inoculated and R5‐inoculated units after the shock loading at 2.0 g l −1 day −1 , whereas the rN7(R503)‐inoculated unit could cope with this shock loading.…”
Section: Resultsmentioning
confidence: 93%